PERTUMBUHAN TANAMAN MENTIMUN (Cucumis sativus L.) MELALUI PEMBERIAN PUPUK KANDANG SAPI DAN PUPUK KANDANG KAMBING - Zul Haedar; Kasifah Kasifah; Irwan Mado; Nurson Petta Pudji (Percetakan Umi Toaha Makassar, 2022)
Cucumber (Cucumis sativus L.) is one of the favored vegetables in Indonesia. Besides being eaten, cucumbers can also be used for cosmetics, medicines and industrial raw materials. To improve the growth quality of cucumber, it is very important to improve the media planting by using organic fertilizers from goat manure and cow manure. The study was conducted using a Randomized Block Design with 2 factors. The first factor is the dose of goat manure with 3 levels which Control; Goat manure 75g/polybag; and Goat manure 150g/polybag. The second factor is the dose of cow manure with 3 levels, Control; Cow manure 75 g/polybag; and Cow manure 150 g/polybag. The results showed that the application of 150 g/polybag of goat manure and 75 g/polybag of cow manure gave the best effect on the vegetative growth of cucumber. The combination between 150 g/polybag of goat manure and 75 g/polybag of cow manure showed the best interaction effect on the number of leaves and root dry weight of cucumber plants.